Enhancing Accountability and Transparency in the Public Sector: A Comprehensive Review of Public Sector Accounting Practices - Mekar Meilisa Amalia (The Es Accounting And Finance, 2023)
This research uses a comprehensive bibliometric analysis to explore the literature on public sector accounting practices and their impact on accountability and transparency. The research used VOSviewer, a bibliometric analysis tool, to visualize and analyze the bibliometric network, revealing patterns of collaboration, influential publications, and key themes. The data collection process yielded 840 scholarly articles from leading academic databases, with a focus on English-language publications in the past decade. The results show six distinct publication clusters, each highlighting significant research themes. Cluster 1 emphasizes innovation and transparency, indicating the relevance of accounting change and performance measurement in public sector organizations. Cluster 2 centers on accounting reform and the adoption of accrual accounting practices, exploring the transition from cash-based to accrual-based accounting in the public sector. Cluster 3 studies forensic accounting and internal audit practices, reflecting the growing interest in fraud detection and risk management in public sector entities. Cluster 4 highlights the importance of information systems and efficiency in public sector accounting. Cluster 5 centers on the pressing issue of corruption in the public sector and the role of audit in combating corrupt practices. Cluster 6 explores the potential application of private sector accounting practices in the public sector. Keyword analysis identified the most frequently occurring keywords, such as "accountant", "public sector reform", "performance", and "service", underscoring their importance in the literature. Conversely, keywords with fewer occurrences, such as "transparency" and "information systems", indicate areas that require further attention and research.